2022
DOI: 10.1186/s12964-022-00831-5
|View full text |Cite
|
Sign up to set email alerts
|

METTL14-mediated N6-methyladenosine modification of ITGB4 mRNA inhibits metastasis of clear cell renal cell carcinoma

Abstract: Background Integrin β4 (ITGB4) participates in tumorigenesis and progression of several malignancies, but its role and related mechanisms in clear cell renal cell carcinoma (ccRCC) remain unclear. Methods Quantitative real-time PCR (qRT-PCR), western blot and immunohistochemistry were used to detect mRNA and protein levels of relevant genes. Biological functions of ITGB4 and methyltransferase-like 14 (METTL14) were determined by in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…METTL3 regulates β-catenin protein expression and membrane localisation in cervical, lung, and liver cancers, thereby promoting cell migration, invasion, and EMT [ 48 ]. Knockdown of METTL14 promotes ITGB4 expression via m6A-YTHDF2, stimulates EMT, and promotes migration, invasion, and metastasis in renal clear cell carcinoma cells [ 49 ]. In breast cancer cells, FTO deletion induces EMT by increasing m6A levels and altering the 3′-terminal processing of key mRNAs along the Wnt signalling cascade [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 regulates β-catenin protein expression and membrane localisation in cervical, lung, and liver cancers, thereby promoting cell migration, invasion, and EMT [ 48 ]. Knockdown of METTL14 promotes ITGB4 expression via m6A-YTHDF2, stimulates EMT, and promotes migration, invasion, and metastasis in renal clear cell carcinoma cells [ 49 ]. In breast cancer cells, FTO deletion induces EMT by increasing m6A levels and altering the 3′-terminal processing of key mRNAs along the Wnt signalling cascade [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that METTL14 plays an anti-oncogenic role by m 6 A modi cation of mRNAs [39,40], miRNAs [41,42] or lncRNAs [43,44], and m 6 A modi cation of circRNAs also takes a part in cancer progression [37,38]. Our previous study authenticated that METTL14-mediated m 6 A modi cation of circORC5 inhibits GC progression [15].…”
Section: Discussionmentioning
confidence: 54%
“…Studies of m 6 A readers in RCC have mainly focused on the YTHDF1, YTHDF2, YTHDC1, and IGF2BPs. Several aspects of the role and mechanism of YTHDF1, YTHDF2, YTHDC1, and IGF2BPs in RCC have been explained in the previous sections ( Ying et al, 2021 ; Shen et al, 2022a ; Xu et al, 2022a ; Shen et al, 2022b ; Chen et al, 2022 ; Liu et al, 2022c ; Liu et al, 2022d ; Zhang et al, 2022 ). Recent studies have reported that YTHDF1-3 could act as tumour markers in RCC.…”
Section: Role Of M 6 a Regulators In The Progressi...mentioning
confidence: 99%
“…Most studies have demonstrated that lower METTL14 expression in RCC tissues is negatively associated with a poor prognosis. METTL14 can act as a tumour suppressor ( Zhang et al, 2021b ; Shen et al, 2022a ; Liu et al, 2022c ; Liu et al, 2022d ; Zhang et al, 2022 ). However, some researchers have opposite conclusions ( Chen et al, 2022 ).…”
Section: Role Of M 6 a Regulators In The Progressi...mentioning
confidence: 99%
See 1 more Smart Citation